Green HRM Sebagai Fondasi Workplace Well-Being: Evaluasi Dimensi Organisasional, Teknologi Dan Regulasi - Hutasuhut, Julianto; Mutholib, Mutholib; Rahmat, Muhammad; Waruwu, Khamo; Sihite, Frans Antoni; Dalimunthe, Ritha F. (JOURNAL ECONOMICS AND STRATEGY, 2025)
The advancement of Industry 4.0 has introduced complex challenges in occupational safety and health, calling for strategic approaches to ensure sustainable work environments. This study aims to analyze the implementation of Green Human Resource Management (Green HRM) in enhancing workplace well-being in Indonesia. Using a Systematic Literature Review (SLR) approach, this study synthesizes relevant scholarly literature published between 2015 and 2025, focusing on Green HRM, workplace well-being, and occupational health and safety (OHS) across key national industries. The findings indicate a positive correlation between Green HRM practices and improved employee well-being, encompassing physical, mental, social, and environmental aspects of the workplace. This relationship is influenced by organizational factors such as OHS systems, workload, and conflict management, and is supported by digital technology and regulatory frameworks. The study formulates an integrative Green HRM model consisting of six core dimensions: green recruitment and selection, green training and development, green performance management, green compensation and benefits, integrated OHS management systems, and enabling technologies. This model offers a holistic framework for creating transformative and sustainable workplace well-being, aligned with the AKHLAK core values and the national development vision of Golden Indonesia 2045.